Association between sitting time and high-sensitivity C-reactive protein level among obese women - Daud, Azlina; Jamal, Anis Fsehah; Shahadan, Siti Zuhaidah (Elsevier Espana, S.L.U., 2021)
Abstract The objective of this study was to determine the time spent on sitting per day, level of serum High sensitivity C-reactive protein (hs-CRP), and the association between sitting time and level of serum hs-CRP among obese women. A descriptive cross-sectional study was conducted. Sixty eight (68) obese women were recruited. They were signed informed consent form prior to the questionnaire answered. Then, sample blood test was taken to check for hsCRP level. Sitting time spent in hours was found to be not significantly associated with hs-CRP level (p = 0.391) among obese women. Longer sitting time spent per day more than 4 h is the factor of obesity and hs-CRP level will be higher in obese women compared to normal people. This study can be baseline data for healthcare professionals and may contribute to develop awareness platform on maintaining normal body mass index among women.